Effective X-ray micro computed tomography imaging of carbon fibre composites. (1st June 2023) - Zwanenburg, E.A.; Norman, D.G.; Qian, C.; Kendall, K.N.; Williams, M.A.; Warnett, J.M.
Abstract: Compression moulding of carbon fibre sheet moulding compounds is an attractive manufacturing method for composite structures. Investigating fibre orientation, defects and voids in these components is important for quality control. X-ray computed tomography is a non-destructive imaging method used on different kind of sheet moulded compound to identify such issues, but it is still a challenge on carbon fibre sheet moulding compound due to the similarities in density of the carbon fibres and polymer matrix. This study aims to determine the best-practice for optimising acquisition parameters for imaging carbon fibre composites. The first experiment assessed the effect of excess material on a region of interest scans was investigated, a common acquisition approach to maintain resolution to resolve fibres. This showed in this specific case the scan quality decreases when surrounding material reaches approximately 75% of the field of view indicating region of interest scanning is feasible. In the second experiment seven X-ray computed tomography parameters were systematically evaluated to optimise image quality for observing the structures and defects, resulting in 168 scans. The results indicate that the source–detector distance and the source voltage have the most significant impact, where users should always consider maximising this distance and minimising voltage for the best image quality.